THE INCORPORATION OF DIGITAL LITERACY IN EFL LEARNING MATERIALS ON JUNIOR HIGH SCHOOL - Palupi, Tara Mustikaning; Subianto, Kurniawan Aji (Indonesian EFL Journal, 2024)
: In the 21st century, digital literacy is deemed crucial for sustaining social life, especially in the realm of education. This significance extends to English as a Foreign Language (EFL) learning, where students' language acquisition abilities are believed to thrive in a digitally literate environment. Despite its importance, research on the integration of digital literacy into EFL learning materials is scant. This study addresses this gap by investigating the presence of digital literacy in EFL learning materials in one junior high school in Jakarta. Utilizing a qualitative approach with content analysis, the researcher examined 33 learning materials from three English teachers, drawing on seven digital literacy components. The findings reveal a comprehensive incorporation of digital literacy components in all analyzed English learning materials. Functional skills emerged prominently, constituting 45% of occurrences, followed by critical thinking and problem-solving skills at 34%. The prevalence of these components is attributed to the predominant use of digital resources in crafting learning materials. Notably, digital literacy is most concentrated in the assignment component, followed by the content component, indicating that teachers effectively guide students in achieving learning goals through properly structured assignments that emphasize digital literacy. Overall, the study underscores the integral role of digital literacy in EFL education and highlights opportunities for enhancing students' skills in evaluating digital information and addressing challenges associated with digital technology.Keywords: Digital Literacy; English learning materials; junior high school